Mechanism of Membrane Curvature Sensing by Amphipathic Helix Containing Proteins - Cui, Haosheng (The Biophysical Society, 2011)
There are several examples of membrane-associated protein domains that target curved membranes. This behavior is believed to have functional significance in a number of essential pathways, such as clathrin-mediated endocytosis, which involve dramatic membrane remodeling and require the recruitment of various cofactors at different stages of the process. This work is motivated in part by recent experiments that demonstrated that the amphipathic N-terminal helix of endophilin (H0) targets curved membranes by binding to hydrophobic lipid bilayer packing defects which increase in number with increasing membrane curvature. Here we use state-of-the-art atomistic simulation to explore the packing defect structure of curved membranes, and the effect of this structure on the folding of H0. We find that not only are packing defects increased in number with increasing membrane curvature, but also that their size distribution depends nontrivially on the curvature, falling off exponentially with a decay constant that depends on the curvature, and crucially that even on highly curved membranes defects large enough to accommodate the hydrophobic face of H0 are never observed. We furthermore find that a percolation model for the defects explains the defect size distribution, which implies that larger defects are formed by coalescence of noninteracting smaller defects. We also use the recently developed metadynamics algorithm to study in detail the effect of such defects on H0 folding. It is found that the comparatively larger defects found on a convex membrane promote H0 folding by several kcal/mol, while the smaller defects found on flat and concave membrane surfaces inhibit folding by kinetically trapping the peptide. Together, these observations suggest H0 folding is a cooperative process in which the folding peptide changes the defect structure relative to an unperturbed membrane.